Research on pragmatic impairment in autistic children during the past two decades (2001–2022): hot spots and frontiers—based on CiteSpace bibliometric analysis - Liu, Yanqin; Tian, Xin; Mao, Haoran; Cheng, Lulu; Wang, Peng; Gao, Yang (Frontiers in Psychology, 2024)
Pragmatic impairment has become a critical aspect of language development in autistic children, gaining significant academic attention over the past two decades. This study leverages bibliometric methods to conduct an exhaustive analysis of literature derived from Web of Science database.Utilizing CiteSpace software, we construct a knowledge map to dissect the academic hotspots in research related to pragmatic impairment in autistic children. This enables us to delineate the evolutionary trajectory of this research domain, analyze the prevailing research dimensions, and anticipate potential future dimensions. Our findings indicate that research hotspots in this field over the past two decades predominantly concentrate on assessing and diagnosing pragmatic impairment in autistic children, intervention strategies, and theory of mind. The research scope on pragmatic impairment in autistic children has been progressively broadened and deepened. Research has evolved from initial descriptions and interpretations of autism to exploring the theory of mind in highfunctioning, school-aged children. The current emphasis is on examining the specific skills these children possess.Autism Spectrum Disorder (ASD) is a pervasive neurodevelopmental disorder that influences approximately 1% of the global populace, with a notable upward trend across a broad spectrum of geographic and sociodemographic groups (1). ASD is primarily characterized by challenges in social communication, constricted interests, and repetitive behaviors, all of which culminate in suboptimal social interaction capabilities for those on the spectrum. It is critical to recognize that ASD, in particular, exhibits a high incidence rate among children. In the United States, approximately 1 in 36 children is affected by ASD (2), whereas in China, according to the Report on the Development Status of the Autism Education and Rehabilitation Industry in China (III), the figure has surpassed 10 million, with over 200 thousand increasing every year (3). Among children on the autism spectrum, their language development is notably impacted from a pragmatic perspective. When viewed through this lens, autistic children often experience various incomplete stages in language processing and usage(4,5). Those difficulties, evident in social communication among those with autism, often manifest as verbal or nonverbal challenges. These individuals typically struggle with social conventions and with shifting